2003
DOI: 10.21836/pem20030406
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and echocardiographic follow-up study in warm-blood horses with heart valve insufficiency

Abstract: ZusammenfassungBei 31 Warmblutpferden mit Herzklappeninsuffizienzen wurden die klinischen und echokardiographischen Befunde der kardiologischen Erst-und Nachuntersuchung im Untersuchungsintervall von zwei bis acht Jahren verglichen. Die Pferde wurden als Turnier-(n = 14), Freizeitpferde (n = 16) und als Zuchtpferd (n = 1) genutzt. Insgesamt wurden bei der Erstuntersuchung 13 Pferde mit Leistungsabfall vorgestellt. Bei den meisten Patienten (n = 25) lag primär eine Mitralklappeninsuffizienz vor. Dabei handelte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…On the other hand, very little is known about the association between these two findings in horses. Gehlen et al [ 34 ] found that the dimensions and grade of murmurs increased from the first to the second examination in a follow-up examination of warmblood horses. However, no direct link between these findings could be detected [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, very little is known about the association between these two findings in horses. Gehlen et al [ 34 ] found that the dimensions and grade of murmurs increased from the first to the second examination in a follow-up examination of warmblood horses. However, no direct link between these findings could be detected [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gehlen et al [ 34 ] found that the dimensions and grade of murmurs increased from the first to the second examination in a follow-up examination of warmblood horses. However, no direct link between these findings could be detected [ 34 ]. In our study, the mean murmur intensity in horses with dimensional changes was 3.3/6 and, therefore, higher than in those without dimensional changes in which mean murmur intensity was 2.5/6.…”
Section: Discussionmentioning
confidence: 99%